Neurodiversity Awareness or Diagnostic Contagion in the Age of TikTok: A Digital Qualitative Study of ADHD Autism and Self Diagnosis Content - Nabil Aflah Tajuddin (Punggawa Global Research: Jurnal Multidisiplin, 2026)
TikTok has become a prominent site where users encounter psychological language about ADHD, autism, masking, sensory strain, executive dysfunction, and neurodivergent identity. Short-form videos can make neurodevelopmental experiences more visible and socially intelligible, especially for users whose difficulties have been dismissed, misnamed, or treated as personal failure. Yet the same accessibility can blur the boundary between self-recognition and clinical assessment. Using secondary digital qualitative content analysis, public TikTok videos were examined as communicative units composed of spoken narration, captions, on-screen text, hashtags, creator positioning, engagement indicators, and visible audience responses. The analysis found three connected patterns. First, neurodiversity content often worked as accessible psychological language by translating clinical categories into everyday experiences of work, school, family, and social interaction. Second, symptom generalisation and diagnostic cueing emerged when ordinary difficulties were framed through viewer-directed captions, checklist structures, and weak clinical qualification. Third, audience uptake shaped diagnostic meaning after publication, as comments could intensify peer validation, invite assessment-oriented inquiry, or reintroduce caution through lay correction. Diagnostic contagion is therefore better understood as a discursive pathway rather than a claim about the social spread of ADHD or autism. The findings shift attention from content accuracy alone to diagnostic usability, showing how platform form can make psychological labels emotionally persuasive and socially available before clinical uncertainty has been examined.